Pemberian Edukasi dalam Upaya Prevensi Diare pada Masyarakat di Tempat Pembuangan Akhir (TPA) Air Dingin Kota Padang - Erlinengsih Erlinengsih; Novia Zulfa Hanum; Sevilla Ukhtil Huvaid (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The density of flies outside the house in settlements around TPA Air Cold which tends to be high can cause environmental-based diseases, especially diarrhea. Diarrhea is a threat to the community in the landfill area because the seeds of the disease can be carried by flies from the garbage and then contaminate food. This service activity aims to increase the knowledge and motivation of the community in the Air Cold TPA area of Padang City in preventing diarrheal diseases. The service method used is providing education through counseling activities, discussions, and holding questions and answers about the material to get door prizes. Participants in this activity include people who live in the TPA area, totaling 160 people. The results obtained in this activity showed encouraging things because the participants responded positively and were very enthusiastic about participating in the counseling activities. Based on the results of the discussion, it was also seen that there was a change in the form of increasing participants' knowledge, this was proven by the correct answers given by the participants in the questions and answer session.